Climate Security Pathway Analysis: Senegal - Madurga Lopez, Ignacio M.; Santa Cruz, Leonardo Medina; Liebig, Theresa Ines; Carneiro, Bia; Pacillo, Grazia; Läderach, Peter R.D. (CGIAR FOCUS Climate Security, 2022)
Rising temperatures, increasing rainfall variability and ocean acidification are reducing crop yields, livestock productivity and fish stocks with detrimental effects over livelihoods and food security (as illustrated in the pathways). The Sahelian drought of the 1970s and 1980s proved to have a devastating impact, particularly for rural communities who witnessed the loss of land, the reduced availability of water resources, crop losses, livestock death and an overall intensification of food insecurity. Many of these rural households were forced to migrate to the main urban centres. At the present, worsening climate conditions and the increasing number of extreme weather events may, once again, have a strong detrimental impact on natural resources availability as well as on livelihoods by exacerbating existing risks and vulnerabilities. This impact can be categorised in two main pathways: - Livelihood and food insecurity (Pathway #1). - Resource availability and access (Pathway #2). This paper presents these pathways in detail